Human Muscular Function during Dynamic Exercise (Medicine and Sport Science, 1995)
During exercise and training, muscular function plays a central role, not only in how we perform but also in how we respond physiologically to a variety of strains. Although muscular function has been frequently investigated in animal models, it has rarely been fully examined under the conditions of human locomotion. This book brings together newly acquired information from a wide range of experiments showing for the first time exactly how human muscles respond and perform during physical activity. Four key sections present readers with an excellent source of knowledge on muscle energetics, efficiency, adaptation, and fatigue and damage. Among the many topics discussed, it examines the ability of humans to sustain and generate mechanical power output during human locomotion and looks at how body mass and other factors influence the mechanics of distance running. It will become a lasting reference for sport scientists, coaches, physicians and athletes.